2021
DOI: 10.3892/mmr.2021.11862
|View full text |Cite
|
Sign up to set email alerts
|

Simiaosan alleviates the symptoms of gouty arthritis via the NALP3/IL‑1β pathway

Abstract: Previous studies have suggested that the herbal medicine simiaosan has beneficial effects on gouty arthritis (GA), for which conventional Western medicines are insufficient (particularly in cases of multiple episodes). The objective of the present study was to investigate the mechanism by which simiaosan alleviated the symptoms of GA. Sprague-Dawley rat models of acute GA were successfully established, as verified by pathological analyses. Additionally, an NLR family pyrin domain containing 3 (NLRP3) overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…e Zishui Tiaogan Decoction was different from the Zishui Qinggan Decoction in that it was mainly used to invigorate the kidney and was supplemented by Qinggan [23]. In addition to Si Miao San, Achyranthes bidentata and Poria cocos were added to make Simiao powder more effective in dehumidifying [24]. Adding Zhibai Dihuang Pills can nourish yin and invigorate the kidney and consolidate the clinical effect.…”
Section: Discussionmentioning
confidence: 99%
“…e Zishui Tiaogan Decoction was different from the Zishui Qinggan Decoction in that it was mainly used to invigorate the kidney and was supplemented by Qinggan [23]. In addition to Si Miao San, Achyranthes bidentata and Poria cocos were added to make Simiao powder more effective in dehumidifying [24]. Adding Zhibai Dihuang Pills can nourish yin and invigorate the kidney and consolidate the clinical effect.…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 levels of patients with alcoholic liver injury and gouty arthritis were significantly increased, indicating that NLRP3 inflammasome was activated in alcoholic liver injury and gouty arthritis ( Wu et al, 2017 ; Chang et al, 2019 ). Similarly, the levels of IL-1β in plasma were positively correlated with the severity of alcoholic liver injury and gouty arthritis ( Ilyas et al, 2019 ; Zhang et al, 2021 ). At the same time, NLRP3 inflammasome further aggravates alcoholic liver injury and gouty arthritis by activating plenty of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 β also has been implicated in bone destruction and bone erosion in GA [ 15 ]. In view of this, some in-depth studies have revealed that the herbal medicine simiaosan can alleviate the symptoms of GA by regulating the NALP3/IL-1 β signaling pathway, and that curcumin can suppress the expression of Nod-like receptor 3 (NLRP3) inflammasome to downregulate the level of IL-1 β via inhibiting the activation of nuclear factor-kappa B (NF- κ B) signaling pathway in monosodium urate (MSU)-induced GA [ 19 , 20 ]. Anyway, there is an urgent need and important clinical value to develop inhibitors targeting IL-1 β in GA with better efficacy and fewer side effects.…”
Section: Introductionmentioning
confidence: 99%